2018
DOI: 10.3390/su10114132
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the RCS’s Application in the Value Added Tax Collecting Process on the Perception of SME Taxpayer in Korea’s Trade Activity: Transparency and Fairness in Trade

Abstract: Value Added Tax (VAT) is the largest source of global tax revenue. However, it faces issues of tax avoidance, such as the black-market and missing trader intra-community fraud. Many studies have postulated that the introduction of the Reverse Charge System (RCS) will contribute to the enhancement of transparency and fairness in trade for small and medium enterprises (SMEs) that supply goods or provide services. This study analyzes SME taxpayers' perception of transparency and fairness in trade resulting from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Oraka, Okegbe, and Ezejiofor [17] investigated the effect of value added tax on the Nigerian economy from 2003 to 2015 using a simple regression analysis. The study found evidence that VAT has a negative relationship with per capita income, while a positive relationship existed between VAT and the government total revenue.…”
Section: Review Of Related Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Oraka, Okegbe, and Ezejiofor [17] investigated the effect of value added tax on the Nigerian economy from 2003 to 2015 using a simple regression analysis. The study found evidence that VAT has a negative relationship with per capita income, while a positive relationship existed between VAT and the government total revenue.…”
Section: Review Of Related Studiesmentioning
confidence: 99%
“…Individuals who get involved in the informal sector evade all manner of tax payment [15], which consequently and negatively affects government public service delivery [16]. According to [17], VAT is the leading source of global tax proceeds, but it is confronted with the challenges of tax avoidance due to shadow economic activities and corruption among business participants. However, this study examines the effect of indirect taxes on consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Their research was based on foreign trade data, as well, this time between Germany and Austria. To mention a non-European research initiative in this area of expertise, a poll run by Yoon [47] among South Korean small and medium-sized dealers in copper, gold and steel scrap indicated a positive effect of RCM on trade transparency and fairness.…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%